E-Learning Based Islamic Religious Education of Learning Media: Alternative Solutions for Online Learning During Covid-19 - Siti Yumnah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The outbreak of the corona virus in early March has until now hit the State of Indonesia. This has a negative impact on the productive sectors in the country’s development, economy, social community, religious activities, and especially the Islamic religious education sector. The purpose of this article is, first, to determine the effectiveness of online IRE (Islamic Religious Education) learning in schools. Second, to find out implementing e-learning based IRE learning. This paper uses a research library research method by analyzing the results of previous research that are relevant to the theme. The results that students feel satisfied and comfortable when expressing ideas and questions through online learning. In addition, the use of online learning media can increase independence in learning. In the implementation process, during the COVID-19 pandemic, Islamic religious education learning to use e-learning is very effective in online learning.